2016
DOI: 10.1111/jnc.13544
|View full text |Cite
|
Sign up to set email alerts
|

2‐Methylcitric acid impairs glutamate metabolism and induces permeability transition in brain mitochondria

Abstract: Accumulation of 2-methylcitric acid (2MCA) is observed in methylmalonic and propionic acidemias, which are clinically characterized by severe neurological symptoms. The exact pathogenetic mechanisms of brain abnormalities in these diseases are poorly established and very little has been reported on the role of 2MCA. In the present work we found that 2MCA markedly inhibited ADP-stimulated and uncoupled respiration in mitochondria supported by glutamate, with a less significant inhibition in pyruvate plus malate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Whereas Amaral et al could not confirm an altered glutamine synthetase activity; they demonstrated that 2‐methylcitric acid inhibited glutamate dehydrogenase activity towards the formation of α‐ketoglutarate in rat brain mitochondria, through competition with glutamate. This affects the availability of α‐ketoglutarate for proper functioning of the citric acid cycle.…”
Section: Effects Of Accumulating Toxic Metabolitesmentioning
confidence: 88%
See 1 more Smart Citation
“…Whereas Amaral et al could not confirm an altered glutamine synthetase activity; they demonstrated that 2‐methylcitric acid inhibited glutamate dehydrogenase activity towards the formation of α‐ketoglutarate in rat brain mitochondria, through competition with glutamate. This affects the availability of α‐ketoglutarate for proper functioning of the citric acid cycle.…”
Section: Effects Of Accumulating Toxic Metabolitesmentioning
confidence: 88%
“…This affects the availability of α‐ketoglutarate for proper functioning of the citric acid cycle. In addition, Amaral et al demonstrated that 2‐methylcitric acid induced mitochondrial permeability transition pore opening, that ultimately led to mitochondrial energy dysfunction, as illustrated by decreased ATP synthesis.…”
Section: Effects Of Accumulating Toxic Metabolitesmentioning
confidence: 99%
“…Some researchers reported on the dysfunction of mitochondrial energy metabolism in patients with MMA and PA . Patients with MMA had mitochondrial abnormalities, reduced oxygen uptake, significantly lowered enzyme activities including cytochrome C oxidase, and respiratory chain complexes I‐IV in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these two routes, two more processes contribute to excitotoxicity. First, glutamate dehydrogenase activity is inhibited by 2‐methylcitric acid . Glutamate oxidation is reduced, ATP production is reduced and the glutamine/glutamate ratio is altered, also inducing excitotoxicity .…”
Section: Complicationsmentioning
confidence: 99%
“…First, glutamate dehydrogenase activity is inhibited by 2‐methylcitric acid . Glutamate oxidation is reduced, ATP production is reduced and the glutamine/glutamate ratio is altered, also inducing excitotoxicity . Second, oxidative stress (both reactive oxygen species [ROS] and reactive nitrogen species) leads to decreased Na + /K + /ATPase activity, mitochondrial depolarization and decreased ATP synthesis, again promoting excitotoxicity.…”
Section: Complicationsmentioning
confidence: 99%